2016
DOI: 10.1002/eji.201646375
|View full text |Cite
|
Sign up to set email alerts
|

Increased autophagy in CD4+ T cells of rheumatoid arthritis patients results in T‐cell hyperactivation and apoptosis resistance

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease hallmarked by aberrant cellular homeostasis, resulting in hyperactive CD4+ T cells that are more resistant to apoptosis. Both hyperactivation and resistance to apoptosis may contribute to the pathogenicity of these T cells in the autoimmune process. A better knowledge of the mechanisms determining such impaired homeostasis could contribute significantly to both the understanding and the treatment of the disease. Here we investigated whether autophagy, is dysre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 22 publications
6
60
2
Order By: Relevance
“…Naive CD4 + T lymphocytes from patients with rheumatoid arthritis have been reported to exhibit autophagic defects that are secondary to a metabolic reprogramming that affects glycolysis 221 . By contrast, CD4 + T cells from patients with rheumatoid arthritis reportedly display increased autophagic responses, hence resembling CD4 + T lymphocytes that are activated in vitro 222 . Whether this apparent discrepancy reflects the CD4 + T cell subset under consideration (naive versus total or activated CD4 + T cells) or a methodological bias remains unclear.…”
Section: Autophagy As a Therapeutic Targetmentioning
confidence: 92%
See 2 more Smart Citations
“…Naive CD4 + T lymphocytes from patients with rheumatoid arthritis have been reported to exhibit autophagic defects that are secondary to a metabolic reprogramming that affects glycolysis 221 . By contrast, CD4 + T cells from patients with rheumatoid arthritis reportedly display increased autophagic responses, hence resembling CD4 + T lymphocytes that are activated in vitro 222 . Whether this apparent discrepancy reflects the CD4 + T cell subset under consideration (naive versus total or activated CD4 + T cells) or a methodological bias remains unclear.…”
Section: Autophagy As a Therapeutic Targetmentioning
confidence: 92%
“…Whether this apparent discrepancy reflects the CD4 + T cell subset under consideration (naive versus total or activated CD4 + T cells) or a methodological bias remains unclear. Irrespectively, HCQ limits the resistance to apoptosis displayed by CD4 + T cells from patients with rheumatoid arthritis ex vivo and reduces disease severity in a mouse model of collagen-induced arthritis 222 . In addition, the specific deletion of Atg5 from mouse CD4 + T cells limits their proliferation and activation ex vivo 222 .…”
Section: Autophagy As a Therapeutic Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now generally agreed upon by many investigators that a chronic state of inflammation is, in part, responsible for driving and perpetuating the progression of RA (reviewed in [94]) and OA (reviewed in [58,164]). Moreover, additional recent evidence has indicated that both apoptosis and an altered state of autophagy are critical events in chronic musculoskeletal disorders, such as RA and OA [60,[102][103][104][105][164][165][166][167]. Although the loss of chondrocyte vitality…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In addition to reviews on how ageing affects immunity and immune monitoring in renal transplantation , our primary clinical papers cover topics as diverse as tumor biology , tissue‐specific inflammation , and autoimmune diseases such as rheumatoid arthritis and Sjögren's syndrome . That these articles represent scientific output not only from Europe , including the United Kingdom , but also collaborations between scientists in Europe, Asia and America , research in Australia and in China is a clear indication of the global appeal and reach of our Journal. I am particularly pleased to say that a forthcoming translational article on checkpoint inhibition in cancer immunotherapy has also been featured in news media .…”
mentioning
confidence: 99%